Strong-viscosity air-guiding release film and manufacturing method thereof

By using biaxially oriented polyester film as the substrate in the release film, combined with adhesives and air-conducting layers of specific components, and utilizing UV curing and laser etching technologies, the technical limitations of release films in balancing high adhesion and air permeability have been overcome. This has achieved a balance between high adhesive strength and air permeability, improving product assembly accuracy and surface flatness.

CN120988607APending Publication Date: 2025-11-21HANGZHOU AIPULAI LOGO MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511314476.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-15
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing release films have technical limitations in balancing high adhesion and air permeability, making them difficult to apply in high-precision fields. Conventional release films are prone to forming bubbles or local voids at the adhesion interface, affecting product assembly accuracy and surface smoothness.

Method used

Using biaxially oriented polyester film as the substrate, combined with an adhesive layer of acrylate pressure-sensitive adhesive and porous alumina microparticles, and an air-conducting functional layer of modified polysiloxane resin and graphene aerogel microparticles, a serpentine microchannel is formed through UV curing and laser etching technology, thereby achieving a unity of adhesive performance and air-conducting function.

Benefits of technology

This technology achieves high adhesion strength and air-permeable release film, ensuring the precision of product assembly and surface flatness, and expanding its application range in high-precision fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120988607A_ABST
    Figure CN120988607A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of functional film material preparation, in particular to a high-viscosity air-guiding release film and a manufacturing method thereof.The manufacturing method comprises the following steps that S1, a two-way stretching polyester film is subjected to corona treatment to form a base material layer; s2, adhesive coating liquid is prepared; s3, coating the adhesive coating liquid on the surface of the base material layer to form an adhesive layer; s4, preparing a gas guide layer coating liquid; s5, coating the adhesive layer with a gas guide layer coating liquid to form a gas guide functional layer matrix; s6, a snakelike micro-channel is machined in the surface of the air guide functional layer base body formed in the step S5; and S7, carrying out hot pressing treatment, and rolling to obtain the finished release film. According to the invention, through collaborative design of a multi-layer structure and precise control of process parameters, compatibility of strong adhesion performance and a controllable gas guide function is realized, and the problem that gas discharge of an existing release film is limited in a high-viscosity state is solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of functional film material preparation, and in particular to a strong-adhesion gas-conducting release film and a manufacturing method thereof. BACKGROUND

[0002] With the rapid development of the fields of precision electronic manufacturing, optoelectronic device packaging, and new energy component assembly, the demand for release films with high adhesion, stable peeling performance, and gas-conducting function is increasing; traditional release films usually use biaxially stretched polyester film as a substrate, and achieve temporary adhesion to the target surface by coating a pressure-sensitive adhesive layer.

[0003] However, in the process of electronic device bonding and display module assembly, if the covered surface has gas retention, the adhesive layer and functional layer of the conventional release film are difficult to effectively conduct the gas, and bubbles or local voids are easily formed at the adhesion interface, affecting the product assembly precision and surface flatness; at the same time, the existing release film has technical limitations in balancing high adhesion and gas-conducting function, and often reduces the adhesion strength when increasing the gas-conducting function, which restricts its application range in high-precision fields. Therefore, there is an urgent need for a strong-adhesion gas-conducting release film and a manufacturing method thereof to solve the above problems SUMMARY

[0004] Based on the above purpose, the present application provides a strong-adhesion gas-conducting release film and a manufacturing method thereof.

[0005] A strong-adhesion gas-conducting release film, comprising a substrate layer, an adhesive layer, and a gas-conducting functional layer, wherein the substrate layer is selected from biaxially stretched polyester film.

[0006] Optionally, the adhesive layer is composed of the following raw materials in percentage by weight: 65-75% of acrylate pressure-sensitive adhesive; 8-12% of porous alumina microparticles; 1-2% of crosslinking agent; 0.3-0.8% of silane coupling agent; 2-4% of photoinitiator; the balance being organic solvent; The gas-conducting functional layer is composed of the following raw materials in percentage by weight: 50-65% of modified polysiloxane resin; 5-8% of graphene aerogel microparticles; 0.1-0.3% of perfluoropolyether leveling agent; the balance being dimethylbenzene / acetone mixed solvent with a volume ratio of 2:1.

[0007] A manufacturing method of a strong-adhesion gas-conducting release film, comprising the following steps: S1: The biaxially stretched polyester film is treated by corona treatment to increase the surface energy to a predetermined value, and then cleaned to form a base layer; S2: The acrylic ester pressure-sensitive adhesive is dissolved in an organic solvent, and porous alumina particles are uniformly dispersed, and then a crosslinking agent, a silane coupling agent and a photoinitiator are added to form a homogeneous adhesive coating liquid; S3: The adhesive coating liquid of S2 is uniformly coated on the surface of the base layer treated in S1, and after volatilizing part of the solvent by pre-drying, UV light curing is performed to form an adhesive layer; S4: The modified polysiloxane resin is dissolved in a mixed solvent of xylene / acetone, and graphene aerogel particles are dispersed, and finally a perfluoropolyether leveling agent is added to prepare a gas guiding layer coating liquid; S5: The gas guiding layer coating liquid of S4 is coated on the adhesive layer cured in S3, and dried to form a gas guiding functional layer substrate; S6: Laser etching technology is used to process a serpentine microchannel on the surface of the gas guiding functional layer substrate formed in S5; S7: The composite film treated in S6 is subjected to heat pressing treatment to promote the chemical bonding between the interfaces of the layers, and finally the finished product is wound.

[0008] Optionally, S1 specifically comprises: S11: Select a biaxially stretched polyester film with a thickness of 12-25 μm as the initial base material and expand it to a tensioned state; S12: The expanded polyester film is treated by a corona treatment device, the treatment power is controlled to be 400-800 W, and the treatment time is controlled to be 1-3 s, so that the surface free energy corresponding to the dyne value is increased to 38-42 dyn / cm; S13: After the corona treatment is completed, the surface is cleaned of particulate matter using an electrostatic adsorption type dust removal device, and the drying control temperature is controlled to be 45-60°C to obtain a base layer with stable dyne value.

[0009] Optionally, S2 specifically comprises: S21: The acrylic ester pressure-sensitive adhesive is weighed according to the predetermined proportion, added to an organic solvent composed of a mixture of ethyl acetate and isopropyl alcohol in a volume ratio of 2:1, the stirring speed is controlled to be 300-500 rpm, and the stirring is continued for 30 minutes to form a homogeneous sol solution; S22: The porous alumina particles are added according to the predetermined proportion, and are treated by ultrasonic dispersion for 15 minutes, with the ultrasonic power controlled to be 200-400 W; S23: The crosslinking agent, the silane coupling agent and the photoinitiator are sequentially added according to the predetermined proportion, and the stirring is continued for 20 minutes until the components are fully and uniformly mixed to obtain a stable adhesive coating liquid.

[0010] Optionally, the S3 specifically comprises: S31: uniformly apply the adhesive coating solution obtained in S2 to the surface of the substrate layer treated in S1 by a coating machine, control the coating thickness to be 10-25 μm, and the coating speed to be 5-15 m / min, to form a to-be-cured coating layer; S32: perform pre-baking treatment on the coated composite film, use a hot air circulating oven, control the temperature to be 60-80 °C, and the time to be 30-90 seconds, so that the surface of the coating layer reaches a semi-dry state; S33: place the pre-baked composite film in a UV curing device for UV irradiation curing, control the light intensity to be 1000-2000 mJ / cm², and the irradiation time to be 2-8 seconds, to promote the cross-linking reaction initiated by the photoinitiator, and form an adhesive layer.

[0011] Optionally, the S4 specifically comprises: S41: weigh the modified polysiloxane resin according to a predetermined proportion, add it to a solvent composed of dimethylbenzene and acetone mixed at a volume ratio of 2:1, continuously stir at a stirring speed of 400-600 rpm for 30 minutes, until the resin is fully dissolved; S42: add graphene aerogel particles to the solution obtained in S41 according to a predetermined proportion, use a high-shear dispersion device for treatment, control the shear rotation speed to be 3000-6000 rpm, and the treatment time to be 10-20 minutes, to uniformly disperse the graphene aerogel particles in the system; S43: add a perfluoropolyether leveling agent to the dispersion system in S42 according to a predetermined proportion, stir again for 15 minutes, and finally prepare a stable gas guide layer coating solution.

[0012] Optionally, the S5 specifically comprises: S51: uniformly apply the gas guide layer coating solution obtained in S4 to the surface of the adhesive layer formed in S3 by a coating device, control the coating thickness to be 5-15 μm, and the coating speed to be set to 3-10 m / min; S52: perform drying treatment on the composite film coated in S51, use a hot air circulating drying device, control the temperature to be 70-90 °C, and the drying time to be 60-120 seconds, to form a gas guide functional layer substrate.

[0013] Optionally, the S6 specifically comprises: S61: fix the gas guide functional layer substrate obtained in S5 on a laser etching platform, set the scanning path to be a predetermined serpentine pattern, control the pattern line width to be 20-50 μm, and the line spacing to be 100-300 μm; S62: surface etching is carried out by using a pulsed ultraviolet laser, the laser wavelength is 355 nm, the single pulse energy is controlled to be 10 muJ to 30 muJ, the scanning speed is set to be 50 mm / s to 150 mm / s, and a continuous snake-shaped microchannel is formed on the surface of the gas guide layer by means of point-by-point etching; S63: after etching is completed, the surface of the gas guide functional layer is subjected to airflow sweeping, and residual particles and microchips are removed.

[0014] Optionally, the S7 specifically comprises: S71: the composite film processed in S6 is sent into a hot pressing treatment device, the hot pressing roller temperature is set to be 90 DEG C to 120 DEG C, the hot pressing pressure is 0.2 MPa to 0.5 MPa, and the transmission speed is controlled to be 1 m / min to 3 m / min. S72: after hot pressing is completed, the composite film is cooled to 20 DEG C to 30 DEG C through a cooling roller, the tension is controlled to be 8 N to 15 N to realize synchronous winding, and a finished product release film is obtained.

[0015] The present application has the following beneficial effects: The present application realizes the organic unity of adhesion performance and interface controllability by constructing a three-layer composite structure composed of a substrate layer, an adhesive layer and a gas guide functional layer, relying on the high dimensional stability of the biaxially oriented polyester film, and combining the filling effect of the porous aluminum oxide particles and the surface modification formula design in the acrylate pressure sensitive adhesive system.

[0016] The present application realizes the rapid crosslinking film formation of the adhesive layer by using UV light curing in the manufacturing process, processes the snake-shaped microchannel on the surface of the gas guide functional layer by means of laser etching technology, and promotes the chemical bonding between the multilayer structure by hot pressing treatment, so as to ensure the overall structural stability and processing continuity of the composite film. BRIEF DESCRIPTION OF DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the present application or prior art, the following will briefly introduce the drawings needed to be used in the embodiments or prior art description. Obviously, the drawings in the following description only illustrate the present application, and other drawings can also be obtained by those skilled in the art without any creative effort.

[0018] Figure 1 The figure is a schematic diagram of the release film manufacturing method of the present application. DETAILED DESCRIPTION

[0019] The application will be described in detail below with reference to the drawings and specific embodiments. It should be noted that, in order to make the embodiments more detailed, the following embodiments are the best, preferred embodiments, and other alternative ways can also be used by those skilled in the art to implement them; and the drawings are only used to describe the embodiments in more detail, and are not intended to specifically limit the application.

[0020] It should be noted that in the specification, "one embodiment", "embodiment", "exemplary embodiment", "some embodiments" and the like indicate that the described embodiment can include a specific feature, structure or property, but not necessarily every embodiment includes this specific feature, structure or property. In addition, when a specific feature, structure or property is described in combination with an embodiment, it should be within the knowledge of those skilled in the related art to implement such a feature, structure or property in combination with other embodiments (whether or not explicitly described).

[0021] Generally, the terms can be understood at least in part from the context in which they are used. For example, depending on the context, the term "one or more" as used herein can be used to describe any feature, structure, or characteristic in the singular or can be used to describe combinations of features, structures, or characteristics, whether large or small, that are combinable by one of ordinary skill in the art. In addition, the term "based on" can be understood as not necessarily intended to convey exclusivity in a set of factors, but rather, at least in part, depending on the context, to allow for the existence of other factors not necessarily expressly described.

[0022] Embodiment 1 A strong-adhesion air-conducting release film, comprising a substrate layer, an adhesive layer and an air-conducting functional layer, the substrate layer is selected from a biaxially stretched polyester film.

[0023] The adhesive layer is composed of the following raw materials in percentage by weight: The proportion of acrylate pressure-sensitive adhesive is 70%; The proportion of porous alumina microparticles is 10%; The proportion of crosslinking agent is 1.5%; The proportion of silane coupling agent is 0.5%; The proportion of photoinitiator is 3%; The balance is an organic solvent; The air-conducting functional layer is composed of the following raw materials in percentage by weight: The proportion of modified polysiloxane resin is 60%; The proportion of graphene aerogel microparticles is 6%; The proportion of perfluoropolyether leveling agent is 0.2%; The balance is a mixture of xylene / acetone solvents with a volume ratio of 2:1.

[0024] As shown in Figure 1 A manufacturing method of a strong-adhesion air-conducting release film, comprising the following steps: S1: The biaxially stretched polyester film is treated by corona treatment to increase the surface energy to a predetermined value, and then cleaned to form a base layer; S2: The acrylic ester pressure-sensitive adhesive is dissolved in an organic solvent, and porous alumina particles are uniformly dispersed, and then a crosslinking agent, a silane coupling agent and a photoinitiator are added to form a homogeneous adhesive coating liquid; S3: The adhesive coating liquid of S2 is uniformly coated on the surface of the base layer treated in S1, and after volatilizing part of the solvent by pre-baking, UV light curing is performed to form an adhesive layer; S4: The modified polysiloxane resin is dissolved in a mixture of xylene / acetone solvent, and graphene aerogel particles are dispersed, and finally a perfluoropolyether leveling agent is added to prepare a gas guiding layer coating liquid; S5: The gas guiding layer coating liquid of S4 is coated on the adhesive layer cured in S3, and dried to form a gas guiding functional layer matrix; S6: Laser etching technology is used to process a serpentine microchannel on the surface of the gas guiding functional layer matrix formed in S5; S7: The composite film treated in S6 is subjected to heat pressing treatment to promote the chemical bonding between the interfaces of the layers, and finally the finished product is wound into a release film.

[0025] S1 specifically includes: S11: A biaxially stretched polyester film with a thickness of 15 μm is selected as the initial base material and is expanded to a tensioned state to ensure uniform surface flatness; S12: The expanded polyester film is treated by a corona treatment device, with a treatment power of 600 W and a treatment time of 2 s, to increase the surface free energy corresponding to the dyne value to 40 dyn / cm; S13: After corona treatment, the surface is cleaned of particulate matter using an electrostatic adsorption type dust removal device, and the drying control temperature is 50°C to remove residual water vapor and surface contamination, obtaining a base layer with stable dyne value.

[0026] S2 specifically includes: S21: The acrylic ester pressure-sensitive adhesive is weighed according to the predetermined proportion and added to an organic solvent composed of a mixture of ethyl acetate and isopropyl alcohol in a volume ratio of 2:1, the stirring speed is controlled at 400 rpm, and the stirring is continued for 30 minutes to form a homogeneous sol liquid; S22: The porous alumina particles are added according to the predetermined proportion, and ultrasonic dispersion is used for 15 minutes with an ultrasonic power of 300 W to achieve stable suspension distribution of the particles in the sol system; S23: The crosslinking agent, the silane coupling agent and the photoinitiator are added in turn according to the predetermined proportion, and the stirring is continued for 20 minutes until the components are fully and uniformly mixed, obtaining a stable adhesive coating liquid.

[0027] S3 specifically comprises: S31: The adhesive coating solution obtained in S2 is uniformly applied to the surface of the substrate layer treated in S1 by a coating machine, the coating thickness is controlled to be 20 μm, and the coating speed is controlled to be 8 m / min, to form a to-be-cured coating; S32: The coated composite film is subjected to pre-baking treatment, a hot air circulating oven is used, the temperature is controlled to be 70°C, and the time is controlled to be 60 seconds, to volatilize part of the organic solvents in the system and make the surface of the coating reach a semi-dry state; S33: The composite film subjected to pre-baking treatment is placed in a UV curing device for UV irradiation and curing, the light intensity is controlled to be 1500 mJ / cm², and the irradiation time is controlled to be 4 seconds, to promote the cross-linking reaction initiated by the photoinitiator and form an adhesive layer.

[0028] S4 specifically comprises: S41: The modified polysiloxane resin is weighed according to a predetermined proportion, added to a solvent composed of dimethylbenzene and acetone mixed at a volume ratio of 2:1, and continuously stirred at a stirring speed of 500 rpm for 30 minutes, until the resin is fully dissolved to form a clear solution; S42: The graphene aerogel microparticles are added to the solution obtained in S41 according to a predetermined proportion, and a high-shear dispersion device is used for treatment, the shear rotation speed is controlled to be 5000 rpm, and the treatment time is controlled to be 15 minutes, to uniformly disperse the graphene aerogel microparticles in the system; S43: The perfluoropolyether leveling agent is added to the dispersion system in S42 according to a predetermined proportion, and stirred again for 15 minutes, to finally prepare a stable gas guiding layer coating solution for subsequent application operation.

[0029] S5 specifically comprises: S51: The gas guiding layer coating solution obtained in S4 is uniformly applied to the surface of the adhesive layer formed in S3 by using a coating device, the coating thickness is controlled to be 10 μm, and the coating speed is set to be 5 m / min; S52: The composite film after application in S51 is subjected to drying treatment, a hot air circulating drying device is used, the temperature is controlled to be 80°C, and the drying time is controlled to be 90 seconds, to promote the volatilization of the solvent and complete the preliminary shaping of the gas guiding coating, to form a gas guiding functional layer substrate.

[0030] S6 specifically comprises: S61: The gas guiding functional layer substrate obtained in S5 is fixed on a laser etching platform, a preset serpentine pattern is set as the scanning path, the pattern line width is controlled to be 40 μm, and the line spacing is controlled to be 200 μm, to meet the arrangement density requirement of the gas guiding channels; S62: A pulsed UV laser is used for surface etching, the laser wavelength is 355 nm, the single pulse energy is controlled to be 20 μJ, and the scanning speed is set to be 100 mm / s, to form continuous serpentine microchannels on the surface of the gas guiding layer by point-by-point etching. S63: After etching is completed, the surface of the air guiding functional layer is blown by airflow to remove residual particles and chippings, so as to ensure that the micro-channel structure is permeable and the contour boundary is complete.

[0031] S7 specifically comprises: S71: The composite film after S6 is sent to a hot pressing treatment device, the temperature of the hot pressing roller is set to 110°C, the hot pressing pressure is set to 0.3 MPa, and the transmission speed is controlled to be 2 m / min, so that the composite film realizes interfacial contact heating in a continuous hot pressing state; during the hot pressing process, the interfacial active groups between the adhesive layer and the air guiding functional layer and the substrate layer are excited to react chemically by the synergistic effect of temperature and pressure, so as to form a stable interfacial bonding structure; S72: After hot pressing is completed, the composite film is cooled to 25°C by a cooling roller, the tension is controlled to be 10 N for synchronous winding, and a finished product release film is obtained.

[0032] Example 2 The formula composition is as follows: The adhesive layer: acrylate pressure-sensitive adhesive 65%, porous alumina particles 8%, crosslinking agent 1%, silane coupling agent 0.3%, photoinitiator 2%, and the rest is organic solvent (ethyl acetate / isopropyl alcohol=2:1); The air guiding functional layer: modified polysiloxane resin 50%, graphene aerogel particles 5%, perfluoropolyether leveling agent 0.1%, and the rest is dimethylbenzene / acetone mixed solvent (volume ratio 2:1).

[0033] The preparation steps are as follows: S1: A biaxially stretched polyester film with a thickness of 12 μm is selected, and after being unfolded to a tensioned state, a treatment power of 400 W is applied by a corona treatment device, and the treatment time is 1 second, so that the surface energy value is increased to 38 dyn / cm; after corona treatment is completed, the surface particles are removed by an electrostatic adsorption dust removal device, and the surface energy is stabilized by drying in a hot air environment at 45°C, to form a treated substrate layer; S2: The acrylate pressure-sensitive adhesive is weighed according to the proportion, added into the mixed solvent of ethyl acetate and isopropyl alcohol, stirred at 300 rpm for 30 minutes to form a homogeneous sol liquid; then the porous alumina particles are added, and an ultrasonic dispersion device with a power of 200 W is used for treatment for 15 minutes; then the crosslinking agent, the silane coupling agent and the photoinitiator are sequentially added, and the stirring is continued for 20 minutes, to obtain a stable and uniform adhesive coating liquid; S3: The adhesive coating liquid is uniformly applied to the surface of the substrate layer at a coating thickness of 10 pm and a speed of 5 m / min to form a to-be-cured coating layer; then it is sent into a hot air circulating oven, the temperature is set to 60°C, and the drying time is 30 seconds to reach a semi-dry state; finally, it is irradiated by a UV curing device at an illumination intensity of 1000 mJ / cm² for 2 seconds to promote the cross-linking reaction initiated by the photoinitiator, and a cured adhesive layer is formed; S4: The modified polysiloxane resin is taken and added into a mixed solvent of xylene and acetone, and stirred at 400 rpm for 30 minutes to fully dissolve; then the graphene aerogel particles are added, and a high-shear dispersion device is used for dispersion treatment, the shear rotation speed is set to 3000 rpm, and the dispersion time is 10 minutes; then the perfluoropolyether leveling agent is added, and stirred for 15 minutes to prepare a gas guiding layer coating liquid; S5: The gas guiding layer coating liquid is uniformly applied to the surface of the cured adhesive layer by using a coating device at a thickness of 5 pm and a speed of 3 m / min; then it is sent into a hot air drying device, the drying temperature is controlled to be 70°C, and the time is 60 seconds to completely dry the coating layer to form a gas guiding functional layer matrix; S6: The dried gas guiding functional layer matrix is fixed on a laser etching platform, the scanning path is set to a snake pattern, the pattern line width is 20 pm, and the line distance is 100 pm; a pulsed ultraviolet laser with a wavelength of 355 nm is used for etching, the single pulse energy is set to 10 pJ, and the scanning speed is 50 mm / s, and a continuous snake-shaped microchannel is formed by point-by-point etching; after etching, a gas flow sweeping device is used to remove surface residual particles and microchips; S7: The etched composite film is sent into a hot pressing treatment device, the hot roller temperature is set to 90°C, the hot pressing pressure is 0.2 MPa, and the transmission speed is 1 m / min, and the interface is treated by hot pressing; after treatment, the composite film temperature is reduced to 20°C by a cooling roller, and is synchronously wound under the condition of a tension of 8 N to obtain a finished release film.

[0034] Example 3 The formula composition is as follows: Adhesive layer: acrylate pressure-sensitive adhesive 75%, porous alumina particles 12%, crosslinking agent 2%, silane coupling agent 0.8%, photoinitiator 4%, and the rest is organic solvent (ethyl acetate / isopropyl alcohol=2:1); Gas guiding functional layer: modified polysiloxane resin 65%, graphene aerogel particles 8%, perfluoropolyether leveling agent 0.3%, and the rest is xylene / acetone mixed solvent (volume ratio 2:1).

[0035] The preparation steps are as follows: S1: Select a biaxially stretched polyester film with a thickness of 25 μm, expand it to a tensioned state, and then apply a treatment power of 800 W through a corona treatment device. The treatment time is 3 seconds, and the surface of the film is treated to increase the surface energy to 42 dyn / cm. After the corona treatment is completed, use an electrostatic adsorption dust removal device to remove surface particles, and dry the surface energy in a hot air environment at 60°C to form a treated base layer; S2: Weigh the acrylic ester pressure-sensitive adhesive according to the proportion, add it to a mixed solvent of ethyl acetate and isopropyl alcohol, and stir at 500 rpm for 30 minutes to form a homogeneous sol solution. Then add porous alumina particles and use an ultrasonic dispersion device with a power of 400 W to treat for 15 minutes. Then add the crosslinking agent, silane coupling agent, and photoinitiator in sequence, and continue stirring for 20 minutes to obtain a stable and uniform adhesive coating liquid. S3: Apply the above-mentioned adhesive coating liquid to the surface of the base layer at a coating thickness of 25 μm and a speed of 15 m / min to form a to-be-cured coating layer. Then send it into a hot air circulation oven, set the temperature to 80°C, and dry for 90 seconds to reach a semi-dry state. Finally, irradiate it with a UV curing device at an illumination intensity of 2000 mJ / cm² for 8 seconds to promote the crosslinking reaction initiated by the photoinitiator and form an adhesive layer. S4: Take the modified polysiloxane resin, add it to a mixed solvent of xylene and acetone, and stir at 600 rpm for 30 minutes to fully dissolve it. Then add graphene aerogel particles and use a high-shear dispersion device to disperse them, with a shear rotation speed of 6000 rpm and a dispersion time of 20 minutes. Then add a perfluoropolyether leveling agent and stir for another 15 minutes to prepare a gas guiding layer coating liquid. S5: Use a coating device to uniformly apply the gas guiding layer coating liquid to the surface of the cured adhesive layer at a thickness of 15 μm and a speed of 10 m / min. Then send it into a hot air drying device, control the drying temperature to 90°C, and dry for 120 seconds to completely dry the coating layer and form a gas guiding functional layer substrate. S6: Fix the dried gas guiding functional layer substrate on a laser etching platform, set the scanning path to a snake pattern with a pattern line width of 50 μm and a line spacing of 300 μm. Use a pulsed ultraviolet laser with a wavelength of 355 nm to etch, set the single pulse energy to 30 μJ, and the scanning speed to 150 mm / s. Form continuous snake-shaped microchannels by point-by-point etching. After etching, use an air flow sweeping device to remove surface residual particles and micro debris. S7: Send the etched composite film into a hot pressing treatment device, set the hot roller temperature to 120°C, the hot pressing pressure to 0.5 MPa, and the transmission speed to 3 m / min, and perform interface hot pressing treatment. After treatment, lower the temperature of the composite film to 30°C by a cooling roller, and simultaneously wind it under a tension of 15 N to obtain a finished release film.

[0036] Comparative Example 1 Step 1: Select a polypropylene film with a thickness of 20 μm, spread and tension at room temperature, without corona treatment, directly as the coating substrate; Step 2: Add 5% silicone oil and 2% white oil to the toluene / isopropyl alcohol mixed solvent (volume ratio 1:1), stir for 10 minutes at 300 rpm to obtain a uniform coating solution; use a coating machine to apply to the surface of the substrate at a thickness of 15 μm and a speed of 5 m / min; Step 3: The coated film is dried at 60°C under hot air conditions for 60 seconds, and the finished release film is directly wound.

[0037] Table 1 Performance parameter comparison of finished release film As can be seen from the above Table 1, Example 1 is superior to Example 2, Example 3 and Comparative Example 1 in various key performance indicators, showing the best overall performance; Specifically, in terms of adhesion performance, the initial adhesion of Example 1 reaches 18 N / 25mm, which is much higher than that of Comparative Example 1, which is 9 N / 25mm, and also shows excellent adhesion strength in the 180° peeling force test; In terms of air guiding performance, Example 1 has a micro-channel structure processed by laser, and the air guiding rate reaches 5.2 mL / min·cm², while Comparative Example 1 does not design air guiding structure, and the air guiding performance is 0; In the high temperature aging test, the peeling force retention rate of Example 1 reaches 95%, which is significantly better than that of Comparative Example 1, which is 60%; In terms of structure consistency, the micro-channel yield reaches 99.3%, indicating that the laser etching and hot pressing process is controlled accurately, which is much higher than the yield level of Example 2 and Example 3; The interlayer peeling force of the composite layer is 20 N / 25mm, indicating that the layers are tightly combined after hot pressing treatment, and are not easy to delaminate or interface peel; The surface energy uniformity is good (CV value 2.1%), indicating that the treated substrate layer has uniform and controllable surface energy, which is conducive to the stable adhesion of the coating layer.

[0038] In summary, Example 1 combines excellent structure design, formula system and process parameters, and is the best performance embodiment in the present application, which is significantly better than Comparative Example 1 representing the conventional process, and is also better than Example 2 and Example 3 in multiple key performance indicators, and has stronger industrial promotion value and application prospect.

[0039] The present application encompasses any substitutions, modifications, equivalent methods and solutions made to the essence and scope of the present application. In order for the public to have a thorough understanding of the present application, specific details are described in the following preferred embodiments of the present application, and the present application can also be completely understood without these details for those skilled in the art. In addition, in order to avoid unnecessary confusion to the essence of the present application, well-known methods, processes, procedures, elements and circuits, etc. are not described in detail.

[0040] The above description is only the preferred embodiment of the present application, it should be pointed out that for those skilled in the art, without departing from the principles of the present application, can make several improvements and refinements, these improvements and refinements should also be considered as the protection scope of the present application.

Claims

1. A highly adhesive, gas-permeable release film, characterized in that, It includes a substrate layer, an adhesive layer, and an air-conducting functional layer, wherein the substrate layer is selected from biaxially oriented polyester film.

2. The strongly adhesive, gas-conducting release membrane according to claim 1, characterized in that, The adhesive layer is composed of the following raw materials by weight percentage: Acrylic pressure-sensitive adhesive accounts for 65-75%; Porous alumina particles account for 8-12%; Crosslinking agent content: 1-2%; The proportion of silane coupling agent is 0.3-0.8%; Photoinitiator accounts for 2-4%; The remainder is organic solvent; The air-conducting functional layer is composed of the following raw materials in weight percentage: Modified polysiloxane resin accounts for 50-65%; Graphene aerogel particles account for 5-8%; The proportion of perfluoropolyether leveling agent is 0.1-0.3%; The remainder is a xylene / acetone mixed solvent with a volume ratio of 2:

1.

3. A method for manufacturing a highly adhesive, gas-conducting release film according to any one of claims 1-2, characterized in that, Includes the following steps: S1: The biaxially oriented polyester film is subjected to corona treatment to increase its surface dyne value to a predetermined value, followed by cleaning and dust removal to form a substrate layer; S2: Dissolve the acrylic pressure-sensitive adhesive in an organic solvent, add porous alumina particles and disperse evenly, then add a crosslinking agent, silane coupling agent and photoinitiator to form a homogeneous adhesive coating liquid; S3: The adhesive coating liquid of S2 is evenly coated onto the surface of the substrate layer treated by S1. After pre-baking to evaporate some of the solvent, it is cured by UV light to form an adhesive layer. S4: Dissolve the modified polysiloxane resin in a xylene / acetone mixed solvent, add graphene aerogel particles for dispersion, and finally add perfluoropolyether leveling agent to prepare an air-conducting layer coating solution. S5: Apply the gas-conducting layer coating liquid of S4 onto the adhesive layer after S3 has been cured, and dry it to form the gas-conducting functional layer matrix; S6: Using laser etching technology, serpentine microchannels are processed on the surface of the gas-conducting functional layer substrate formed by S5; S7: The composite film after S6 treatment is subjected to hot pressing to promote chemical bonding between the interlayer interfaces, and finally wound up to obtain the finished release film.

4. The method for manufacturing a highly adhesive, gas-conducting release film according to claim 3, characterized in that, S1 specifically includes: S11: Select a biaxially oriented polyester film with a thickness of 12μm to 25μm as the initial substrate and unfold it to a taut state; S12: The unfolded polyester film is passed through a corona treatment device, with the treatment power controlled at 400W to 800W and the treatment time at 1s to 3s, so that the dyn value corresponding to its surface free energy is increased to 38 to 42 dyn / cm. S13: After the corona treatment is completed, an electrostatic adsorption dust removal device is used to clean the particulate matter on its surface, and the drying temperature is controlled at 45℃ to 60℃ to obtain a substrate layer with a stable dyne value.

5. The method for manufacturing a highly adhesive, gas-conducting release film according to claim 3, characterized in that, S2 specifically includes: S21: Weigh the acrylic pressure-sensitive adhesive according to the preset ratio, add it to the organic solvent composed of ethyl acetate and isopropanol in a volume ratio of 2:1, control the stirring speed to 300 rpm to 500 rpm, and continue stirring for 30 minutes to form a homogeneous sol solution. S22: Add porous alumina particles according to the preset ratio, and treat with ultrasonic dispersion for 15 minutes, controlling the ultrasonic power to be 200W to 400W; S23: Add the crosslinking agent, silane coupling agent and photoinitiator in sequence according to the preset ratio, and continue stirring for 20 minutes until all components are fully and evenly mixed to obtain a stable adhesive coating liquid.

6. The method for manufacturing a highly adhesive, gas-conducting release film according to claim 3, characterized in that, S3 specifically includes: S31: Apply the adhesive coating liquid obtained in S2 evenly to the surface of the substrate layer treated in S1 using a coating machine, controlling the coating thickness to be 10μm to 25μm and the coating speed to be 5m / min to 15m / min, to form a coating to be cured. S32: Pre-dry the coated composite film using a hot air circulating oven, controlling the temperature at 60℃ to 80℃ for 30 to 90 seconds, so that the coating surface reaches a semi-dry state. S33: The pre-baked composite film is placed in an ultraviolet curing device for UV curing. The light intensity is controlled at 1000mJ / cm² to 2000mJ / cm², and the irradiation time is 2 to 8 seconds. This promotes the photoinitiator to initiate a cross-linking reaction and cures to form an adhesive layer.

7. The method for manufacturing a highly adhesive, gas-conducting release film according to claim 3, characterized in that, S4 specifically includes: S41: Weigh the modified polysiloxane resin according to the preset ratio, add it to the solvent composed of xylene and acetone in a volume ratio of 2:1, and stir continuously for 30 minutes at a stirring speed of 400 rpm to 600 rpm until the resin is fully dissolved. S42: Add graphene aerogel particles to the solution obtained in S41 according to a preset ratio, and process it with a high shear dispersion device. The shear speed is controlled at 3000 rpm to 6000 rpm, and the processing time is 10 minutes to 20 minutes, so that the graphene aerogel particles are uniformly dispersed in the system. S43: Add perfluoropolyether leveling agent to the S42 dispersion system according to the preset ratio, stir again for 15 minutes, and finally prepare a stable air-conducting layer coating liquid.

8. The method for manufacturing a highly adhesive, gas-conducting release film according to claim 3, characterized in that, S5 specifically includes: S51: Apply the gas-conducting layer coating liquid obtained in S4 evenly to the surface of the adhesive layer formed in S3 using a coating device, controlling the coating thickness to be 5μm to 15μm and the coating speed to be 3m / min to 10m / min. S52: The composite film after S51 coating is dried using a hot air circulating drying device, with the temperature controlled at 70℃ to 90℃ and the drying time at 60 to 120 seconds, to form the gas-conducting functional layer substrate.

9. The method for manufacturing a highly adhesive, gas-conducting release film according to claim 3, characterized in that, S6 specifically includes: S61: Fix the gas-conducting functional layer substrate obtained in S5 onto the laser etching platform, set the scanning path to a preset serpentine pattern, control the pattern line width to 20μm to 50μm, and control the line spacing to 100μm to 300μm. S62: A pulsed ultraviolet laser is used for surface etching. The laser wavelength is 355nm, the single pulse energy is controlled between 10μJ and 30μJ, and the scanning speed is set between 50mm / s and 150mm / s. A continuous serpentine microchannel is formed on the surface of the gas guide layer by point-by-point etching. S63: After etching, the surface of the gas-conducting functional layer is purged with airflow to remove residual particles and micro-debris.

10. The method for manufacturing a highly adhesive, gas-conducting release film according to claim 3, characterized in that, Specifically, S7 includes: S71: The composite film after S6 treatment is fed into the hot pressing device. The temperature of the hot pressing roller is set to 90℃ to 120℃, the hot pressing pressure is 0.2MPa to 0.5MPa, and the transmission speed is controlled at 1m / min to 3m / min. S72: After hot pressing, the composite film is cooled to 20°C to 30°C by cooling rollers, and the tension is controlled at 8N to 15N for synchronous winding to obtain the finished release film.